2021
DOI: 10.1111/ner.13339
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Capsule/Ventral Striatum Stimulation in Obsessive-Compulsive Disorder: Toward a Unified Connectomic Target for Deep Brain Stimulation?

Abstract: Introduction Obsessive‐compulsive disorder (OCD) is among the most disabling chronic psychiatric disorders and has a significant negative impact on multiple domains of quality of life. Deep brain stimulation (DBS) is a treatment option for severe therapy‐resistant OCD. Objective To provide a detailed clinical description and treatment outcome analysis in a cohort of eight refractory OCD patients receiving ventral capsule/ventral striatum (VC/VS) stimulation with the intention to validate discriminating fiber b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
(55 reference statements)
3
31
0
Order By: Relevance
“…An independent research group confirmed the predictive value of the pathway in 10 subjects with OCD and DBS of the ALIC/VS applying the same analysis procedure (32). A second group re-calculated an optimal tract using the same methodology on a novel sample eight patients and identified the same bundle in direct comparison to the published one (33). The significant association between clinical improvement and the extent of modulating this specific pathway was reproduced in both studies (32,33).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
See 4 more Smart Citations
“…An independent research group confirmed the predictive value of the pathway in 10 subjects with OCD and DBS of the ALIC/VS applying the same analysis procedure (32). A second group re-calculated an optimal tract using the same methodology on a novel sample eight patients and identified the same bundle in direct comparison to the published one (33). The significant association between clinical improvement and the extent of modulating this specific pathway was reproduced in both studies (32,33).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…A second group re-calculated an optimal tract using the same methodology on a novel sample eight patients and identified the same bundle in direct comparison to the published one (33). The significant association between clinical improvement and the extent of modulating this specific pathway was reproduced in both studies (32,33).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
See 3 more Smart Citations